Exploring the Dynamics of Instagram Content Marketing and Engagement: Its Impact on YouTube Membership Subscription Decisions - Putri, Arvianti Farah Natsya; Gaffar, Vanessa; -, Lisnawati; Wibowo, Lili Adi; Khairunnisa, Zahra Nadhira (Journal of Business Management Education (JBME), 2025)
The aim of this research is to investigate the influence of content marketing on customer engagement and purchase intention among followers of Jurnalrisa's official Instagram account who have subscribed to the Jurnalrisa YouTube channel. Using path coefficient analysis through Smart PLS, the study found that all hypotheses were supported. The results indicate that content marketing has a positive effect on customer engagement, which in turn also enhances purchase intention. Customer engagement serves as a significant mediating variable, highlighting the importance of customer involvement in the decision-making process. These findings provide valuable insights for marketers to design more effective strategies to boost purchase intention through engaging and relevant content.